Literature across Borders: The Pilot YearPart 2: The Students; Subhi Suvradeep Banerjee, Rupert Barrington, Rebekah Curtis, Dharani Dhavamani, Sarah Dyer, Pooja Kadaboina, Charlotte Taylor, Janette Taylor (Leaf Journal)
This ‘project proceedings’ article comprises eight reflections from students involved in the Pilot Year of the Literature across Borders project, facilitated by The Green Literature Festival (India) between Ashoka University (India) and Bath Spa University (UK). This article pairs with a partner piece (see this issue) outlining the concept, planning, and delivery of the pilot year, and exploring staff reflections.